HUBUNGAN TINDAKAN HEMODIALISIS DENGAN KUALITAS HIDUP PADA PASIEN GAGAL GINJAL KRONIK DI RUANGAN HEMODIALISA DI RSU SEMBIRING - Meta Rosaulina (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
“Chronic kidney failure is a public health problem in the world, where the incidence of chronic renal failure is increasing every year. The increasing number of patients suffering from chronic renal failure will also increase the number of patients undergoing hemodialysis.hemodialysis is a way to replace the work that is usually done by the kidneys, namely cleaning the blood from metabolic waste, toxic substances and removing water deposits in the body. In this study, researchers used a survey analytic method with a cross sectional. The population in this study were 68 respondents, while the sample in this study was taken using accidental sampling namely 30 respondents. From statistical test using the chi-square test obtained p-Value = 0,028 < α = 0,05, where there is a relationship between hemodialysis and quality of life in patients withhh chronic renal failure in the hemoodialysis room of the RSU Sembiring. It is advisable for patients with chronic kidney failure who are undergoing hemodialysis to improve their good quality of life because the quality of life has a significant effect on patients suffering ffrom chronic kidney failure who are undergoing hemodialysis”.